On the aposteriori error estimates for finite‐element solutions - Čiegis, Raimondas (Mathematical Modelling and Analysis, 1998)
The analysis of the accuracy of the aposteriori error estimation procedure for finite‐element solutions is presented. The function Y – y is used as an aposteriori error estimator, here y ∈ S 01, Δ is the finite‐element solution of the given problem and Y ∈ S 0 2, Δ is the high order solution of the same problem. The second order accuracy is proved for this error estimator in the L 2, H 1 and L8 norms. Results of numerical experiments are presented.First Published Online: 14 Oct 2010